THE STUDY OF THE PRAGMATIC OF LANGUAGE FITNESS AT THE CENTRAL MARKET OF POLEWALI MANDAR - NUR HAFSAH YUNUS MS; Sulihin Azis (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2021)
This study aims to determine the form of realization of language politeness that occurs in the Pekkabata Central Market, Polewali Mandar Regency. This type of research is descriptive qualitative research. The method used in this research is a case study with stages; The first stage, preliminary study. The second stage is to define/formulate the problem and determine the focus of the research. The third stage, literature study and research analysis. The fourth stage, collect data. The fifth stage is data processing and interpretation. The sixth stage is to make a research report. Meanwhile, for data collection, it was done by means of interviews, observation, note-taking techniques, listening techniques, and documentation. The results of the study show that 1. There are various forms of language that are not polite and quite impolite spoken by traders and buyers; (2) Deviations from the principle of politeness spoken by traders and buyers violate the maxim of wisdom, the maxim of acceptance, the maxim of generosity, the maxim of humility, the maxim of compatibility and sympathy maxims. The biggest violation is in the maxim of wisdom. This maxim of wisdom outlines each participant of the speech to minimize the losses of others and maximize the benefits of others; and (3) the perception of speakers of languages ​​outside the Pekkabata market such as traders and buyers from various speech circles in the Pekkabata market is mostly not so rude speech.